The Enigmatic Aliphatic Acetogenins and Their Correlations With Lipids During Seed Germination and Leaf Development of Avocado (Persea americana Mill.) - Colin-Oviedo, Álvaro; Garza-Aguilar, Sara M.; Marín-Obispo, Luis Martín; Rodríguez-Sánchez, Dariana Graciela; Trevino, Víctor; Hernández-Brenes, Carmen; Díaz de la Garza, Rocío I. (Frontiers in Plant Science, 2022)
Lipids in avocado have been widely studied due to their nutritional value and several reported bioactivities. Aliphatic acetogenins are a relevant component of the avocado lipidome and have been tested for several potential food and pharma industries applications. This work followed the evolution of avocado fatty acids and aliphatic acetogenins during seed germination and leaf growth. Oil extracts of embryonic axes, cotyledons, and leaves from seedlings and trees were divided to analyze free acetylated acetogenins (AcO-acetogenins), and free fatty acids. Embryonic axes from germinating seeds contained the highest amount of AcO-acetogenins and fatty acids; this tissue also accumulated the most diverse fatty acid profile with up to 22 detected moieties. Leaves presented the highest variations in AcO-acetogenin profiles during development, although leaves from seedlings accumulated the simplest fatty acid profile with only 10 different FAs. Remarkably, AcO-acetogenins represented half of the carbons allocated to lipids in grown leaves, while embryonic axes and cotyledons always contained more carbons within fatty acids during germination. Thus, we hypothesized the use of the AcO-acetogenin acyl chain for energy production towards β-oxidation. Also, -linoleic and docosahexaenoic acids were proposed as close AcO-acetogenin intermediaries based on a correlation network generated using all these data. Another part of the oil extract was fractionated into different lipid classes before transesterification to profile fatty acids and acetogenins bound to lipids. Acetogenin backbones were identified for the first time in triglycerides from cotyledons and mainly in polar lipids (which include phospholipids) in all developing avocado tissues analyzed. Seed tissues accumulated preferentially polar lipids during germination, while triglycerides were consumed in cotyledons. Seedling leaves contained minute amounts of triglycerides, and polar lipids increased as they developed. Results from this work suggest acetogenins might be part of the energy and signaling metabolisms, and membrane structures, underlining the yet to establish role(s) of these unusual lipids in the avocado plant physiology.